KATEGORI TANDA DALAM IKLAN MCDONALD'S ARAB SAUDI DI INSTAGRAM - Jia Ulhaq (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2025)
This study aims to analyze the types of signs and meanings in McDonald's advertisements on the @mcdonaldsksa Instagram account. The research employs a qualitative descriptive method. Data were obtained from McDonald's Saudi Arabia advertisements posted on the @mcdonaldsksa Instagram account. Data collection techniques included observation and documentation. In analyzing the data, researchers applied the extra lingual equivalence method with Roland Barthes' semiotic approach. The results showed that 15 McDonald's Saudi Arabia advertisements on Instagram comprise six categories of signs formed by visual and verbal elements. These signs have both denotative and connotative meanings. The denotative meaning arises from the signifier and signified in the advertisements. In contrast, the connotative meaning encompasses the symbolism of yellow, red, and other colors, the socio-cultural context within the advertisements, the messages and objectives of the advertisements, and rhetorical questions that engage personal aspects. . Keywords: Advertising, Instagram, McDonald’s Saudi Arabia, Semiotics.